THE ELECTROCHEMICAL OXIDATION OF (BENZYLIDENEACETONE)DICARBONYL(PHOSPHINE)IRON(0) AND (BENZYLIDENEACETONE)DICARBONYL(PHOSPHITE)IRON(0) COMPLEXES IN DIMETHYL FORMAMIDE - Nogueira, V. M.; Benedetti, A. V.; Vichi, EJS; Stein, E. (Elsevier B.V., 1991)
The electrochemical oxidation of (benzylideneacetone)dicarbonyl(phosphine)iron(0) and benzylideneacetone)dicarbonyl(phosphite)iron(0) complexes was studied by cyclic voltammetry and controlled potential electrolysis in 0.5 M NaClO4 (dimethyl formamide). The results suggest that the electrode process involves a complicated mechanism, the species formed in the first oxidation step being highly unstable and its decomposition producing free benzylideneacetone, free phosphine or phosphite, solvated iron(II) species and carbon monoxide which adsorbs on the platinum electrode. A linear relationship between E(p/2)ox and the ligand parameter P(L) was obtained with E(s) = 0.41 V and beta = 0.964, where E(s) and beta-denote electron-richness and polarizability of the metal centre, respectively.